Development Of Integrated Elements Chemical Domino Card Game With Ethnochemistry Madura Jamu Ingredients - Astid Putera, Dwi Bagus Rendy (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to develop an elemental chemistry domino card game integrated with the ethnochemistry of Madurese herbal ingredients. The concept raised is an educational game that connects domino card games, elemental chemistry, and natural ingredients of Madurese herbal medicine. The development of this media uses the ADDIE development model. The ADDIE model consists of Analyze, Design, Development, Implementation, and Evaluation stages. The development of this media was carried out with two trials, namely in the form of validation questionnaires and student response questionnaires. The validation test consists of media validation (appearance and program) and material (content and presentation). The response questionnaire consists of indicators of convenience, interest, and usefulness. Media trials were conducted on 30 students of class XII IPA 2 SMAN 3 Pamekasan. The results of this study were the development of an elemental chemical domino card game that was integrated with ethnochemistry on Madurese herbal ingredients with an average percentage of very valid material category validation results (97.19) and very valid media category validation (92.70). The results of the response questionnaire to the elemental chemical domino card trial with indicators of ease, interest, and usefulness of the media obtained an average percentage in the very good category (75). Elemental chemical domino card media integrated with ethnochemistry of Madurese herbal ingredients is very valid for use in learning.